A simple self-assembly nanomicelle based on brain tumor-targeting peptide-mediated siRNA delivery for glioma immunotherapy via intranasal administration. (1st January 2023) - Tang, Lin; Zhang, Rui; Wang, Yusi; Zhang, Xiaoyu; Yang, Yuling; Zhao, Binyan; Yang, Li
Abstract: The blood-brain barrier (BBB) has a key role in preventing drugs from entering the brain. Non-invasive intranasal drug delivery routes that bypass the BBB are increasing in popularity because of their ability to shorten the journey and reduce the loss of genetic drugs such as siRNA in transit. However, the complex synthesis and quality control process of most nose-to-brain delivery carriers and the limited mass production are the main obstacles to their clinical application. Here, we constructed a siRNA delivery system with simple synthesis and quality control methods using cholesterol-modified T7 (T7-C), in which T7 can bind to the transferrin receptor (TfR) expressed on glioma cells to target gliomas. In our results, T7-C had dual functions as a glioma-targeting carrier and immune adjuvant. As a targeted delivery carrier, T7-C intranasally delivered siRNA into the mouse brain through the olfactory bulb pathway and was taken up by glioma cells by the caveolin- and transferrin-dependent pathway. As an immune adjuvant, T7-C could promote DC maturation and combined with slit2 siRNA could promote polarization of M2 subtype macrophages to M1 subtype macrophages and then increase the proportion of effector T cells to remodel the tumor environment. In conclusion, T7-C with glioma targeting as a delivery system of slit2 siRNA showed a good therapeutic effect in the treatment of glioma after intranasal administration and had potential application prospects. Statement of significance: In contrast to the existing literature that uses complex materials to deliver drugs across the blood-brain barrier (BBB) in an invasive manner for glioma treatment, we developed a simple, self-assembling siRNA delivery system (T7-C) based on brain tumor-targeted T7 peptide to treat glioma by intranasal administration. T7-C/siRNA could reach the tumor site through the olfactory bulb route and adjust the "cold" tumor microenvironment to the "hot" tumor microenvironment and non-invasive intranasal delivery route could shorten the journey and reduce the loss of genetic drugs. Therefore, our design has good application prospects and is expected to serve as a general strategy for intranasal drug delivery in the treatment of brain tumors. Graphical abstract: Image, graphical abstract